1998
DOI: 10.1016/s0014-5793(98)00423-2
|View full text |Cite
|
Sign up to set email alerts
|

GLUT4 translocation by insulin in intact muscle cells: detection by a fast and quantitative assay

Abstract: We report a rapid and sensitive colorimetric approach to quantitate the amount of glucose transporters exposed at the surface of intact cells, using L6 muscle cells expressing GLUT4 containing an exofacial myc epitope. Unstimulated cells exposed to the surface 5 fmol GLUT4myc per mg protein. This value increased to 10 fmol/mg protein in response to insulin as 2-deoxyglucose (10 W WM) uptake doubled. The results are substantiated by immunofluorescent detection of GLUT4myc in unpermeabilized cells and by subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
217
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 209 publications
(226 citation statements)
references
References 32 publications
(32 reference statements)
7
217
0
1
Order By: Relevance
“…Cell culture and troglitazone treatment L6GLUT4myc myoblasts were differentiated into myotubes by growing them in α-MEM supplemented with 2% fetal bovine serum as described previously [30]. At a seeding density of 2× 10 4 cells/ml (1 and 2 ml per well in 24-or 12-well plates, respectively) L6 cells fully differentiate into myotubes by day 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture and troglitazone treatment L6GLUT4myc myoblasts were differentiated into myotubes by growing them in α-MEM supplemented with 2% fetal bovine serum as described previously [30]. At a seeding density of 2× 10 4 cells/ml (1 and 2 ml per well in 24-or 12-well plates, respectively) L6 cells fully differentiate into myotubes by day 7.…”
Section: Methodsmentioning
confidence: 99%
“…Detection of surface GLUT4myc or GLUT1myc was performed on intact myotubes as previously described [30]. Briefly, L6-GLUT4myc myotubes or L6-GLUT1myc myotubes grown in 24-well tissue culture plates were treated with vehicle (0.1% DMSO), troglitazone (5 μg/ml) or insulin (100 nmol/l) for 30 min.…”
Section: Immunodetection Of Cell Surface Glut4myc or Glut1mycmentioning
confidence: 99%
“…This disparity between the magnitude of GLUT4 translocation and the stimulation of glucose uptake has been observed in mature skeletal muscle (2)(3)(4)(5), primary adipocytes (6 -8), and muscle and fat cell lines (9,10). Recently, we developed a muscle cell line overexpressing GLUT4 fused to a Myc epitope that becomes exposed at the cell surface, allowing for the detection of GLUT4 translocation in intact cells (11,12). Using this system, we reported that GLUT4 translocation precedes the stimulation of glucose uptake by at least 2 min (13).…”
mentioning
confidence: 99%
“…Detection of Cell Surface GLUT4myc-GLUT4myc levels at the cell surface was measured by an antibody-coupled colorimetric assay as described (11). L6-GLUT4myc myotubes were washed once with PBS, fixed with 3% paraformaldehyde (v/v) for 3 min at room temperature, and then neutralized with 1% (w/v) glycine in PBS at 4°C for 10 min.…”
mentioning
confidence: 99%
“…Plasmid transfection The L6 muscle cell line and hamster kidney fibroblast cell line BHK were maintained in culture [21,22]. Lipofectamine 2000 (Invitrogen, Burlington, ON, Canada) was used for plasmid transfections.…”
Section: Methodsmentioning
confidence: 99%